2003
DOI: 10.1088/0031-9155/48/17/310
|View full text |Cite
|
Sign up to set email alerts
|

Study of the relative dose-response of BANG-3  polymer gel dosimeters in epithermal neutron irradiation

Abstract: Polymer gels have been reported as a new, potential tool for dosimetry in mixed neutron-gamma radiation fields. In this work, BANG-3 (MGS Research Inc.) gel vials from three production batches were irradiated with 6 MV photons of a Varian Clinac 2100 C linear accelerator and with the epithermal neutron beam of the Finnish boron neutron capture therapy (BNCT) facility at the FiR 1 nuclear reactor. The gel is tissue equivalent in main elemental composition and density and its T2 relaxation time is dependent on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…From this study, it is concluded that PAG provides a good simulation of radiation transport in the brain and is very similar to water. In a study of the relative dose–response of BANG-3 polymer gel dosimeters in epithermal neutron irradiation, a good correspondence was found between the measured dose distribution and the calculated dose distribution obtained with a two-dimensional discrete ordinate radiation transport code (DORT) (Uusi-Simola et al 2003). This demonstrates that for the BANG-3 polymer gel, there is no significant change in dose sensitivity due to differences in LET that may occur in this epithermal neutron beam.…”
Section: Applications Of Polymer Gel Dosimetrymentioning
confidence: 94%
“…From this study, it is concluded that PAG provides a good simulation of radiation transport in the brain and is very similar to water. In a study of the relative dose–response of BANG-3 polymer gel dosimeters in epithermal neutron irradiation, a good correspondence was found between the measured dose distribution and the calculated dose distribution obtained with a two-dimensional discrete ordinate radiation transport code (DORT) (Uusi-Simola et al 2003). This demonstrates that for the BANG-3 polymer gel, there is no significant change in dose sensitivity due to differences in LET that may occur in this epithermal neutron beam.…”
Section: Applications Of Polymer Gel Dosimetrymentioning
confidence: 94%
“…A previous gel dosimetry study in epithermal neutron beam had been done with BANG‐3 polymer gel dosimeters (10) . The linear nature of the BANG‐3 response to total absorbed dose in epithermal neutron irradiation was verified, even though part of the dose is induced by high‐LET particles.…”
Section: Introductionmentioning
confidence: 85%
“…The rapid dose falloff in the right edge of the phantom seen in both Figs. 4͑a͒ and 4͑b͒ indicates the effects of oxygen, 36,[41][42][43] which will be discussed later in this section, and the effects of the B1-field inhomogeneity near the edges of the head coil. 3,18,21,22 The erroneous dose buildup in the downstream side of the water-equivalent material seen in those figures stems from the susceptibility effects in MRI images.…”
Section: Discussionmentioning
confidence: 99%